2018
DOI: 10.1016/j.ast.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the formation of resonant tones in compressible cavity flows

Abstract: Identification of the fluid dynamic mechanisms responsible for the formation of resonant tones in a cavity flow is challenging. Time-frequency non-linear analysis techniques were applied to the post-processing of pressure signals recorded on the floor of a rectangular cavity at a transonic Mach number. The results obtained, confirmed that the resonant peaks in the spectrum were produced by the interaction of a carrier frequency (and its harmonics) and a modulating frequency. High-order spectral analysis, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Strouhal numbers are typically associated with velocity fluctuations in the layers of the recirculating flow inside the cavity, whereas higher modes are associated with the formation of sub-eddies inside the stratified layers of the main inner vortex. The interaction of these centrifugal instabilities with the acoustic modes of the shear layer occur due to non-linear quadratic coupling, as shown in previous studies ( [5], [6], [8], [9]) and are responsible for the generation of the Rossiter-Heller tones.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Strouhal numbers are typically associated with velocity fluctuations in the layers of the recirculating flow inside the cavity, whereas higher modes are associated with the formation of sub-eddies inside the stratified layers of the main inner vortex. The interaction of these centrifugal instabilities with the acoustic modes of the shear layer occur due to non-linear quadratic coupling, as shown in previous studies ( [5], [6], [8], [9]) and are responsible for the generation of the Rossiter-Heller tones.…”
Section: Introductionsupporting
confidence: 52%
“…This influenced the evolution of the main recirculatory vortex, and then its instabilities (directly correlated to ), and the shear layer trajectory (responsible for the feedback loop ). Previous studies [9] indicated that these phenomena are strongly non-linear, and minimal external influences could have been the cause of the high sensitivity of the associated central frequencies to even minimal local flow changes. The findings of this study are in line with previous works on the effect of incidence on weapons bay aeroacoustic response [22].…”
Section: Unsteady Flow Analysismentioning
confidence: 99%
“…For the time-frequency domain analysis, the Morlet wavelet transform was used to calculate the wavelet spectral power (WSP) map [27] where,…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…For the characterisation of the statistical non-stationary modes the index of persistence (PR) was used [27]. This index varies from 0 %, indicating that a particular tone is inactive during the time window, to 100 %, indicating that a particular tone is always active during the time window.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…Cavity flow oscillations exist in many aerospace engineering fields [1][2][3][4], such as weapon bays [5,6] and landing gears [7,8]. e physical mechanism in a cavity is complex.…”
Section: Introductionmentioning
confidence: 99%